Effect of Molecular Structure on the Adsorption of Soluble Aromatic Hydrocarbons by Activated Carbon - Yakout1, S.M. (Asian Journal of Chemistry, 2014)
The compounds known as polycyclic aromatic hydrocarbons (PAHs) and benzene, toluene, ethylbenzene and xylene (BTEX) are soluble aromatic hydrocarbons among the most carcinogenic, mutagenic and toxic found in aquatic systems. The effect of adsorbate properties (molecular structure, molecular weight and solubility) on adsorption from liquid phase was studied for the chosen organic substances of aromatic character using rice husk activated carbon (RHAC). The possible mechanisms of adsorption process and solute interactions with carbon surface were analyzed. The effect of substituent in aromatic ring of adsorbate molecule on the adsorption affinity toward carbon surface was regarded. Adsorption increases with decreasing solubility of adsorbent and increases with the molecular weight of the solute. Adsorption rate correlated with number of methyl group in the molecule as well as the length of the side chain.